Implementasi Program STBM Pilar Pertama dalam Penanggulangan Praktik Buang Air Besar Sembarangan di Kabupaten Sekadau - Mariana, Mariana; Maryuni, Sri; Pardi, Pardi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
Open Defecation (OD) practices remain a public health issue in Indonesia, including in Sekadau Regency, which recorded in September 2024 that 70 households still practiced open defecation and 801 households lacked proper sanitation. This study analyzes the implementation of the Community-Based Total Sanitation (STBM) Program, First Pillar (Stop OD), in Sekadau using Purwanto and Sulistyastuti’s policy implementation theory, which covers socialization, execution, and policy outcomes. This descriptive qualitative study involved 6 categories of informants (n=18) through observation, in-depth interviews, and documentation, analyzed with an interactive model and triangulation. The main challenge was the limited number of sanitarians (1 for every 4,515 households). Multi-media communication strategies (print, digital, and face-to-face) effectively reached communities, supported by cross-sector collaboration among government, community leaders, and partners such as World Vision Indonesia. Program success was influenced by five factors: capacity building of sanitarians, contextual communication, innovation in addressing resistance, sustainable collaboration, and adaptive monitoring. The findings highlight the need for an integrated approach in implementing community-based sanitation policies to achieve sustainable Open Defecation Free (ODF) status.